PERANCANGAN PROGRAM APLIKASI PEMBELIAN PADA PT INDO TAICHEN TEXTILE INDUSTRY - Yakub, Yakub; Hermanto, Shirly (Bina Nusantara University, 2010)
PT Indo Taichen Textile Industry is a company in the textile industry producing cloth. Activities and operations personnel administration, payroll systems, purchasing systems, and inventory systems are conducted manually. Problems begin to become fairly complex on the company’s purchasing system so that a software application is required. Purchasing system is made by Data Flow Diagram (DFD) as a model of the process or system and Entity Relation Diagram (ERD) as a data model. The purchasing application is programmed using the programming language Visual Basic 6.0 and SQL Server database.Keywords: data base, purchasing, system, information system